2009
DOI: 10.4161/cam.3.4.9934
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-2 acts as a modulator of Sema3A-dependent glioma cell migration

Abstract: Semaphorin 3A (Sema3A) is a secreted guidance molecule initially described in the nervous system. This protein is able to control axon growth but also effects on endothelial cells migration. Here, we report that Sema3A acts as a chemorepellent factor for the rat C6 glioma cells and three different human glioma cell lines. Interestingly, Sema3A triggered a chemoattractive response in a fourth human glioma cell line. The nature of the receptor complex ensuring the appropriate signaling was dissected in C6 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
(51 reference statements)
2
23
1
Order By: Relevance
“…Long-term analysis of pTM-NRP1 membrane incorporation using confocal microscopy revealed cell-surface clearance of peptide after 96 h (data not shown). Consistent with our previous description of the action mechanism of the peptide (Roth et al, 2008), we found in C6 cells that pTM-NRP1 altered oligomerization of NRP1 on addition of Sema3A (Figure 5a), a semaphorin involved in glioma migration (Nasarre et al, 2009) and shown to promote glioma dispersal through an autocrine mechanism (Bagci et al, 2009). Moreover, although not inducing acute toxicity in C6 cells (see Figure 5b), the addition of pTM-NPR1 induced a significant reduction of cell proliferation (À32%, Po0.05, Figure 5c).…”
Section: Ptm-nrp1 Is An Anti-angiogenic Agentsupporting
confidence: 78%
“…Long-term analysis of pTM-NRP1 membrane incorporation using confocal microscopy revealed cell-surface clearance of peptide after 96 h (data not shown). Consistent with our previous description of the action mechanism of the peptide (Roth et al, 2008), we found in C6 cells that pTM-NRP1 altered oligomerization of NRP1 on addition of Sema3A (Figure 5a), a semaphorin involved in glioma migration (Nasarre et al, 2009) and shown to promote glioma dispersal through an autocrine mechanism (Bagci et al, 2009). Moreover, although not inducing acute toxicity in C6 cells (see Figure 5b), the addition of pTM-NPR1 induced a significant reduction of cell proliferation (À32%, Po0.05, Figure 5c).…”
Section: Ptm-nrp1 Is An Anti-angiogenic Agentsupporting
confidence: 78%
“…Although accumulating evidence has demonstrated a correlation between semaphorin expression and glioma progression (Correa et al, 2001;Rieger et al, 2003;Rich et al, 2005), studies of the expression of plexins and the role of semaphorin-plexin interactions in gliomas remain scanty (Rieger et al, 2003;Bagci et al, 2009;Nasarre et al, 2009;Coma et al, 2010). Here, we show that plexin-B3 is expressed in human glioma cells, which upon activation by its ligand Sema5A inhibits cell motility, triggers cell collapse and promotes ramification of processes.…”
Section: Discussionmentioning
confidence: 89%
“…NRPs associate with plexins to facilitate semaphorin binding and signaling. [12][13][14] They also interact with and modulate the function of VEGFR1 and VEGFR2, 15 as well as other receptors including integrins. [16][17][18] The association of NRPs with specific integrins and the enhancement of integrin function by VEGF/NRP signaling have captured our attention and are the focus of this review.…”
Section: Introductionmentioning
confidence: 99%